The Life Mission Theory V. Theory of the Anti-Self (the Shadow) or the Evil Side of Man - Soren Ventegodt; Niels Jorgen Andersen; Joav Merrick (The Scientific World Journal)
According to the life mission theory, the essence of man is his purpose of life, which comes into existence at conception. This first purpose is always positive and in support of life. This is not in accordance with the everyday experience that man also engages in evil enterprises born out of destructive intentions. This paper presents a theory about the evil side of man, called the anti-self (the shadow), because it mirrors the self and its purpose of life. The core of the anti-self is an evil and destructive intention opposite to the intention behind the life mission. The evil side of man arises when, as the life mission theory proclaims, man is denying his good, basic intention to avoid existential pain. The present theory of the anti-self claims that all the negative decisions accumulated throughout the personal history, sum up to a negative or dark anti-self, as complex, multifaceted, and complete as the self. All the negative decisions taken through personal history build this solid, negative, existential structure. The anti-self, or shadow as Carl Gustav Jung used to call it, is a precise reflection of mans basically good and constructive nature. When mapped, it seems that for most or even for all the many fine talents of man, there is a corresponding evil intention and talent in the persons anti-self. As man is as evil as he is good, he can only realize his good nature and constructive talents by making ethical choices. Ethics therefore seem to be of major importance to every patient or person engaged in the noble project of personal growth. Understanding the nature and structure of the evil side of man seems mandatory to every physician or therapist offering existential therapy to his patient. The theory of anti-self makes it possible to treat patients with destructive behavioral patterns, who want to be good deep in their heart, by helping them let go of their evil intentions. The anti-self also seems to explain the enigma of why human beings often commit suicide. Integrating the shadow often leads to dramatic, subjective experiences of ubiquitous light in an unpersonal form, of enlightenment, or of meeting light and consciousness in a personal, universal form, known as G-d.